The minimalist teacher - Musiowsky-Borneman, Tamera; Arnold, C. Y. (ASCD, 2021)
"Musiowsky-Borneman and Arnold bring a minimalist mindset to the classroom through their three-step decision-making process to declutter the classroom and build a better learning environment"--